PROBLEMATIKA PEMBELAJARAN MUATAN LOKAL PENDIDIKAN LINGKUNGAN HIDUP DI KELAS V SEKOLAH DASAR - Dinata, Serica Aulia; Sastrawati, Eka; Budiono, Hendra (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to describe the problems encountered in teaching the local content subject of Environmental Education (Pendidikan Lingkungan Hidup/PLH) in Class VA of SDN 059/IV Jambi. This research employed a qualitative approach using a case study method, with the research subjects consisting of the homeroom teacher and the VA class students. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles & Huberman. The results revealed several key challenges in teaching environmental education, including limited instructional time (only one lesson hour per week), a lack of relevant learning resources, and insufficiently varied teaching approaches. Other obstacles included the continued implementation of the 2006 KTSP curriculum, which no longer meets students’ current needs. Nevertheless, the teacher strived to address these challenges by utilizing supplementary teaching materials such as educational videos, involving students in practical activities like planting medicinal herbs, and providing contextual explanations tailored to students' needs. The study concludes that despite the challenges, the teacher’s creativity and flexibility enabled the PLH learning process to continue effectively. Recommendations from this study include updating the curriculum, providing more relevant learning media, and increasing parental and community involvement to support environment-based learning.